IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TERHADAP UPAYA PENCEGAHAN TRAFFICKING - Kamudin, Kamudin (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2015)
This thesis discusses about the trying to aborting the trafficking indonesian works especially the women in Indramayu district. Due to in regional or international. The victim of trafficking or slavition, so many policy that made by government to fail the trafficking of women and children, basicly the decissions are relativly comprehensivly, since the Costitution 1945 to the rules below it.The problem about the trafficking to women workers in Indramayu district and act with regional government try in minimallizing of trafficking actions of women works in Indramayu district, analysis that done for failing the trafficking of women workers with a few rules about it.In this thesis discussions, the phenomenas are existing to basic problem that will be mixed with conseptual librariation and the mindset that developed for getting the datas of real using the yuridic and empiric. With the theory for determinating of observations. The thesis is using kualitatif with observation and interview.It is can be summaried that factors are causing the trafficking of women workers in Indramayu district, in regional or international fasilities caused by : poority, low education, the minority of job opportunity and the lifestyle the traffickers joining the nearest people of the living environment, the activities of goverments organitations to non government organitations are followed to minimizing the traffickers actions of women workers in Indramayu district.